The Role of Curriculum Inspector for Implementing and Achieving National Goals of Education in Daily Classroom Activities - Uttam Khanal (Budapest International Research and Critics University, 2023)
The inspector's role has to play in curriculum implementation in classroom activities in community schools. The classroom activities, of course, experiments are not in cases of learning achievement. The effectiveness of proper curriculum implementation has explained the role of resource people. This kind of practice is done at school, in which participation by students, teachers and the whole school environment is used from textbooks to achieve goals of education. The government of Nepal has been doing different types of work at different times to improve the educational quality of community schools. The expected results from that work have not been achieved. Finding ways to improve educational problems is ongoing. Keeping this in mind, the state seemed confident that the successful implementation of the curriculum was also an option. In order to implement it, it was done to identify the course work area and make the resource person responsible for it. In order to fully implement the curriculum at the school level, teachers can not only teach books to students, but also do extra activities, organize examinations and evaluations according to time, choose learning areas and objectives according to order, and facilitate the environment for refresher training for teachers. Apart from this, it was seen from the study that he has a role as a supporting element to move forward as a whole, working as a bridge between teachers, parents and students.